Learning Video Based On Coastal Areas To Increase Mathematical Learning Interest In The Pandemic Covid-19 - Ferryansyah Ferryansyah (Jurnal Pengabdian Masyarakat Borneo, 2022)
During the Covid-19 Pandemic, learning was carried out at the home of each student or Learning From Home (BDR). The new problem that arises is that the stress level of students increases and interest in learning mathematics decreases. To overcome this problem, learning innovation is needed. One of the things that can be done is to use a coastal area-based learning video during the lesson. One of the places to study in the coastal area of Tarakan City is LKP Fajar Mentari. With the existence of this learning video, it can help the community increase their interest in learning mathematics during the Covid 19 pandemic. The method is carried out at the beginning, namely conducting observations and interviews with partners and children on the coast of Amal Beach through direct observation with health protocols or by telephone / whatsaap, then doing license to implement the program ,, prepare a coastal area-based learning video by utilizing the Tarakan Amal Beach environment and objects around the coast. After the video is ready to foster, do face to face with health protocol and link the learning video based on the Amal Beach Tarakan coastal area through online applications WhatsApp. The last stage is to present a questionnaire on the interest in learning mathematics at the end of the community service. The result of the activity, namely children's interest in learning using mathematics learning videos increased during the covid-19 pandemic. This can be seen from the children feeling happy, enthusiastic and active in answering even in learning mathematics.